2020
DOI: 10.1016/j.mbplus.2020.100041
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in extracellular matrix composition during aging and photoaging of the skin

Abstract: Human skin is composed of the cell-rich epidermis, the extracellular matrix (ECM) rich dermis, and the hypodermis. Within the dermis, a dense network of ECM proteins provides structural support to the skin and regulates a wide variety of signaling pathways which govern cell proliferation and other critical processes. Both intrinsic aging, which occurs steadily over time, and extrinsic aging (photoaging), which occurs as a result of external insults such as solar radiation, cause alterations to the dermal ECM. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 83 publications
2
75
0
Order By: Relevance
“…For optimal ECM coverage, the Gnd-HCl/HA extraction protocol is recommended as it produces the greatest number of PSMs and highest sequence coverage of core matrisome proteins. Disease progression and aging have been shown to increase the resistance of the insoluble ECM to extraction, 44 increasing the necessity of effectively extracting the insoluble ECM via chemical digestion. Additionally, the Gnd-HCl/HA extraction produces two separate ECM fractions which can be analyzed independently, further increasing ECM identifications and allowing for assessment of ECM solubility.…”
Section: Discussionmentioning
confidence: 99%
“…For optimal ECM coverage, the Gnd-HCl/HA extraction protocol is recommended as it produces the greatest number of PSMs and highest sequence coverage of core matrisome proteins. Disease progression and aging have been shown to increase the resistance of the insoluble ECM to extraction, 44 increasing the necessity of effectively extracting the insoluble ECM via chemical digestion. Additionally, the Gnd-HCl/HA extraction produces two separate ECM fractions which can be analyzed independently, further increasing ECM identifications and allowing for assessment of ECM solubility.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that downregulation of LOX in the context of ageing is not restricted to the lung. For instance, LOX expression is reduced with age in human, rat and monkey skin ( 153 , 214 , 215 ), in urogenital tissues of female mice ( 216 ) and in rat aorta ( 217 ). Notably, loss of function mutations in LOX predispose to aortic aneurysms and age is the most important risk factor for aortic aneurysms ( 158 , 159 ), supporting the concept that loss of LOX upon ageing may have direct effects on ECM integrity and tissue stiffness.…”
Section: Baseline Changes In Collagen Synthesis and Maturation During Mouse Lung Ageingmentioning
confidence: 99%
“…An immunohistochemical study of human lungs found an age-dependent increase of TIMP2 + cells, but not MMP2 + cells, in the lung ( 249 ), providing some evidence for decreased MMP-mediated collagen degradation in the aged lung. Notably, in a recent pioneering study of human skin ageing, the authors correlated matrisome changes with the assessment of ECM integrity by single harmonic generation and two-photon autofluorescence imaging ( 214 ). Among other changes, they found decreased MMP2 and increased TIMP3 levels in aged skin.…”
Section: Baseline Changes In Collagen Synthesis and Maturation During Mouse Lung Ageingmentioning
confidence: 99%
“…For optimal ECM coverage, the Gnd-HCl/HA extraction protocol is recommended as it produces the greatest number of PSMs and highest sequence coverage of core matrisome proteins. Disease progression and aging have been shown to increase the resistance of the insoluble ECM to extraction ( 46 ), increasing the necessity of effectively extracting the insoluble ECM via chemical digestion. Additionally, the Gnd-HCl/HA extraction produces two separate ECM fractions, which can be analyzed independently, further increasing ECM identifications and allowing for assessment of ECM solubility.…”
Section: Discussionmentioning
confidence: 99%